Tissue-specific circadian clocks in plants. (February 2016) - Endo, Motomu
Highlights: There are multiple circadian oscillators in each type of cell. Circadian clocks in different tissues are hierarchically coupled with each other. A network structure of the plant clock system is proposed. Abstract : Circadian clocks affect a large proportion of differentially expressed genes in many organisms. Tissue-specific hierarchies in circadian networks in mammals have been contentiously debated, whereas little attention has been devoted to the concept in plants, owing to technical difficulties. Recently, several studies have demonstrated tissue-specific circadian clocks and their coupling in plants, suggesting that plants possess a hierarchical network of circadian clocks. The following review summarizes recent studies describing the tissue-specific functions and properties of these circadian clocks and discusses the network structure and potential messengers that might share temporal information on such a network.